(untitled) (Cuidado y Ocupación Humana, 2024)
The Cuidado y Ocupación Humana Journal continues to establish itself as an essential space for open-access digital scientific dissemination. From the Occupational Therapy program at the University of Pamplona, the journal assumes the responsibility of promoting unpublished and innovative research. Each submission undergoes expert peer review, ensuring scientific quality, rigor, and relevance. In this way, the journal highlights the academic and professional work of researchers, faculty, and students, whose contributions enrich the fields of health, education, social sciences, and the humanities.